2015
DOI: 10.1039/c5dt02964c
|View full text |Cite
|
Sign up to set email alerts
|

Polyvinylpyrrolidone (PVP) in nanoparticle synthesis

Abstract: Colloidal synthesis offers a route to nanoparticles (NPs) with controlled composition and structural features. This Perspective describes the use of polyvinylpyrrolidone (PVP) to obtain such nanostructures. PVP can serve as a surface stabilizer, growth modifier, nanoparticle dispersant, and reducing agent. As shown with examples, its role depends on the synthetic conditions. This dependence arises from the amphiphilic nature of PVP along with the molecular weight of the selected PVP. These characteristics can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
930
0
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,386 publications
(967 citation statements)
references
References 215 publications
(449 reference statements)
28
930
0
9
Order By: Relevance
“…Two other peaks at 1290 and 1420 cm ¹1 were also observed in the IR spectra of Sample 1-1 and PVP, which correspond to the CN vibration and CH 2 bending vibration of PVP, respectively. 21) Therefore, the observation of these peaks in Sample 1-1 confirmed that PVP was incorporated into the nanoparticles in this sample. For Samples 1-1 and 5, the peaks at 28002900 cm ¹1 are attributed to CoO and/or ethylene glycol 22), 23) and those at 1100 cm ¹1 are attributed to ethylene glycol.…”
Section: Resultsmentioning
confidence: 65%
“…Two other peaks at 1290 and 1420 cm ¹1 were also observed in the IR spectra of Sample 1-1 and PVP, which correspond to the CN vibration and CH 2 bending vibration of PVP, respectively. 21) Therefore, the observation of these peaks in Sample 1-1 confirmed that PVP was incorporated into the nanoparticles in this sample. For Samples 1-1 and 5, the peaks at 28002900 cm ¹1 are attributed to CoO and/or ethylene glycol 22), 23) and those at 1100 cm ¹1 are attributed to ethylene glycol.…”
Section: Resultsmentioning
confidence: 65%
“…For solution 1, the necessary amount of PVP (three PVP/Pd molar ratios were prepared, 1, 10 and 20) was added to 60 ml of ethylene glycol in a three-neck round-bottom flask and the solution was stirred at 80 °C for 2 h using a magnetic stirrer. For solution 2, 0.112 g (0.5 mmol) of Pd(OAc) 2 were dissolved in 12 ml of 1,4-dioxane by stirring for 2 h at room temperature using also a magnetic stirrer. The color of this solution was light orange.…”
Section: Methodsmentioning
confidence: 99%
“…1,2 Nevertheless, it has also been reported that the capping agents used in colloidal synthesis are not merely stabilisers but also effective additives which modify the final NPs morphology features, not only in terms of NPs size and shape, [3][4][5][6] but also of electronic properties. [7][8][9] Thus, despite this necessity, the impact of these molecules once the metal NPs are synthesised is a difficult issue, as it will affect the catalytic behaviour of metal-based catalytic systems by modifying either the NPs physicochemical properties or their accessibility by creating a physical barrier that hinders the access of reactants to the surface NPs catalytically active sites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] In this last usage, PVP is o en exposed to strong oxidizing agents such as sodium hypochlorite (bleach) during the cleaning of the membrane to remove the bio lms which readily forms at the surface. 4) Such chemical cleaning is not inconsequential and turns out to be deleterious for the membrane, ultimately leading to its degradation.…”
Section: Introductionmentioning
confidence: 99%